Individualized Nutritional Support for Hospitalized Patients With Oropharyngeal Dysphagia After Stroke: A Randomized Controlled Trial - Yan, Xiu-Li; Liu, Zhuo; Sun, Ye; Zhang, Peng; Lu, Xue-Yan; Mu, Fei; Du, Juan; Yang, Yi; Guo, Zhen-Ni (Frontiers in Nutrition, 2022)
Objectives: Post-stroke dysphagia may cause aspiration pneumonia, malnutrition, dehydration, and other complications. However, data on the effects of nutritional supplementation and its value after stroke are insufficient. We aimed to evaluate the effect of an individualized 1-week nutrition intervention program on swallowing function and nutritional status in stroke patients with oropharyngeal dysphagia. Methods: This study comprised the control group receiving oral nutritional support and continuous nasogastric tube feeding according to the results of the water swallow test (WST). The intervention group additionally underwent a volume-viscosity swallowing test (V-VST) and intermittent oroesophageal tube feeding based on WST. The outcomes were measured after 7 days of intervention, including the improvement of swallowing function assessment by WST, biochemical parameters, such as total serum protein, serum albumin, hemoglobin levels and body composition. This trial was registered with the Chinese Clinical Trial Registry, identifier ChiCTR 2100054054. Results: In total, 173 participants completed the study between September 1, 2020, and April 30, 2021. Patients receiving individualized nutritional support showed a more significant improvement in the total effective rate of swallowing function (95.3% vs. 85.1%, P < 0.05). After the intervention, the total serum protein level (0.97 ± 0.41 g/L vs. −0.83 ± 0.47 g/L; P < 0.05), serum albumin level (0.33 ± 0.28 g/L vs. −1.39 ± 0.36 g/L; P < 0.001) and lean tissue mass (0.13 ± 0.35 g/L vs. −1.00 ± 0.40 g/L; P < 0.001) increased in the intervention group. The decrease of hemoglobin levels in the control group was more evident (−6.17 ± 1.63 g/L vs. −0.64 ± 1.40 g/L; 95%CI, −9.78 to −1.28; P = 0.001). The difference of phase angle between the two groups was statistically significant (5.93 ± 0.88  vs. 5.77 ± 0.78 ; P = 0.035), but not in body fat mass. Conclusions: In stroke patients with oropharyngeal dysphagia, the use of individualized nutritional support based on V-VST and intermittent oroesophageal tube feeding during the first week of hospitalization improved swallowing function and maintained nutritional status.